Correlation between sagittal balance and thoracolumbar elastic energy parameters in 42 spines subject to spondylolisthesis or spinal stenosis and 21 normal spines - Bračun, Špela; Romolo, Anna; Rehakova, Veronika; Leban, Jure; Pukšič, Žan; Vengust, Rok; Daniel, Matej; Kralj-Iglič, Veronika; Drab, Mitja (Heliyon, 2024)
The curvature of the lumbar spine plays a critical role in maintaining spinal function, stability, weight distribution, and load transfer. We have developed a mathematical model of the lumbar spine curve by introducing a novel mechanism: minimization of the elastic bending energy of the spine with respect to two biomechanical parameters: dimensionless lumbosacral spinal curvature c LS and dimensionless curvature increment along the spine CI. While most of the biomechanical studies focus on a particular segment of the spine, the distinction of the presented model is that it describes the shape of the thoracolumbar spine by considering it as a whole (non-locally) and thus includes interactions between the different spinal levels in a holistic approach. From radiographs, we have assessed standard geometrical parameters: lumbar lordosis LL, pelvic incidence PI, pelvic tilt PT, sacral slope ψ0 and sagittal balance parameter SB = sagittal vertical axis (SVA)/sacrum-bicoxofemoral distance (SFD) of 42 patients with lumbar spinal stenosis (SS) or degenerative spondylolisthesis (SL) and 21 radiologically normal subjects. SB statistically significantly correlated with model parameters c L5 (r = -0.34, p = 0.009) and -CI (r = 0.33, p = 0.012) but not with standard geometrical parameters. A statistically significant difference with sufficient statistical power between the patients and the normal groups was obtained for c LS, CI, and SB but not for standard geometrical parameters. The model provides a possibility to predict changes in the thoracolumbar spine shape in surgery planning and in assessment of different spine pathologies.
Keywords: Thoracolumbar spine; Spine curvature; Sagittal balance; Lumbar lordosis; Elastic energy